Preface - Francois Tolmie (Acta Theologica)
From text: On 13 and 14 March 2006 twenty-three scholars gathered at the University of the Free State in Bloemfontein, South Africa, for a conference on the rhetorical analysis of the Letter to the Galatians. At that stage thirty years had passed since Hans Dieter Betz published his well-known article “The literary composition and function of Paul’s Letter to the Galatians”. History shows that this article (and his commentary published shortly thereafter) led to an explosion of interest in the rhetorical analysis of this letter. Thirty years later the interest in this issue has not diminished! Over the past few years a number of rhetorical studies of Galatians have been published in which new approaches to the rhetorical analysis of Galatians are proposed. All of this indicated that a conference on this issue could be worthwhile. In the light of recent developments the conference focused, in particular, on new approaches to the rhetorical analysis of Galatians.